ANALISIS KORELASIONAL MINAT HOLLAND DENGAN PILIHAN JURUSAN PERGURUAN TINGGI PADA SISWA SMA N 1 PADANG SAGO - Hermayesi, Hermayesi; Masril, Masril; Fitriani, Wahidah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to evaluate the success of students in determining career choices through the implementation of Holland Theory at SMA N 1 Padang Sago. The background shows that many students face difficulties in choosing their majors, which impacts their motivation and proactivity. The methode of this article uses a quantitative method involving 100 students. By implementing a career planning program based on Holland Theory, students are encouraged to explore their interests and talents that are aligned with six personality types: Realistic, Investigative, Artistic, Social, Entrepreneurial, and Conventional (RIASEC). The results show a significant increase in students' ability to recognize and choose appropriate majors, as well as an increase in their motivation and creativity in planning for the future. Novelty This program effectively helps students overcome career-related challenges and prepares them for a dynamic job market. Technology integration through Google Sites also facilitates interactive access to career information, supporting a more in-depth learning process.